KONTRIBUSI USAHA RUMAHAN ENTING-ENTING TERHADAP PENDAPATAN KELUARGA DI KECAMATAN WATANG PULU KABUPATEN SIDENRENG RAPPANG - S, Agustina; -, Irmayani; Reeng, Arman (Jurnal Ilmiah Ecosystem, 2020)
Enting-enting Home-Based Business Enting-enting's home-based business is carried out by the Watang Pulu District community as a side job to increase capital and where the business is combined with farming, one of which is rice fields. They make the house column as a place of work. The existence of Enting-enting Home-Based Enterprises contributes to the increase in income earned by farmers, because income from farming which is sometimes erratic encourages farmers to increase their income through other complementary activities. This study aims (1) to find out how much Enting-enting Home-Based Business Revenue in Watang Pulu Subdistrict, Sidenreng Rappang Regency (2) for how much the contribution of Enting-enting Home-Based Businesses to Family Income in Watang Pulu District, Sidenreng Rappang Regency focuses on Home Based Business The main enting instruments carried out to collect research data are in the form of a questionnaire that has been designed based on the type of variable data analysis method used, namely by using Qualitative and Quantitative.The results showed the language (1) Enting-enting Home Based Business in Watang Pulu District, Sidenreng Rappang District had an average income of Rp. 396.546/ month. (2) Enting-enting Home-Based Businesses in Watang Pulu District have a Contribution to Family Income which is an average of 15,29%.